Implementasi Kebijakan Sekolah Ramah Anak di Sekolah Dasar Katolik Kota Samarinda - Yunita Filadelvia Hurai Ibo; Lorensius Lorensius (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2023)
This study aims to describe the implementation of Child-Friendly Schools (CFS) policies, especially in efforts to strengthen religious moderation from an anti-violence perspective. This qualitative study uses data collection methods in observation, documentation, and interviews with three informants, then analyzed descriptively. The results of this study indicate that the implementation of CFS has been endeavored to be as good as possible. The principle of implementing this policy is contained in the core values of the school's vision and mission, namely the values of love and care. Implementing CFS policies, especially in strengthening religious moderation from the perspective of non-violence, allows several changes in restorative practices in schools to create superior generations in the future. Anti-violence, if formulated based on the school's vision and mission values, religious and human values, and if implemented in the CFS program, can foster tolerance in students and teach them commendable behavior so they can fight against radicalism.